2022
DOI: 10.1186/s13020-022-00626-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture at acupoints with lower versus higher pain threshold for knee osteoarthritis: a multicenter randomized controlled trial

Abstract: Background The acupoint selections impact the effects of acupuncture, and preliminary evidence showed potential connection between pain threshold (PT) and acupuncture response. This study examined whether acupuncture at acupoints with lower PT versus higher PT would yield different effects in patients with knee osteoarthritis (KOA). Methods In this multicenter randomized clinical trial, patients were randomly assigned (1:1:1) to receive acupuncture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…These points in TCM theory are interpreted as tonifying Qi and Blood, promoting the circulation of meridian channels and collaterals, leading to facilitating joint function recovery. Previous RCTs have also con rmed that acupoint stimulation around the knee joint has a signi cant effect on KOA and improves patients' pressure-pain threshold [53,55], which was consistent with the ndings of our previous study [39]. This multicenter pilot study expands patient recruitment beyond a single hospital setting to minimize regional differences that may exist.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These points in TCM theory are interpreted as tonifying Qi and Blood, promoting the circulation of meridian channels and collaterals, leading to facilitating joint function recovery. Previous RCTs have also con rmed that acupoint stimulation around the knee joint has a signi cant effect on KOA and improves patients' pressure-pain threshold [53,55], which was consistent with the ndings of our previous study [39]. This multicenter pilot study expands patient recruitment beyond a single hospital setting to minimize regional differences that may exist.…”
Section: Discussionsupporting
confidence: 89%
“…The selection of press-points of Tuina treatment are mainly proximal acupoints in previous studies [53]. We referred to the results of data mining and selected the acupoints including Liangqiu (ST34), Neixiyan (EX-LE4), Dubi (ST35), and Xuehai(SP10) on the front of the thigh and Weizhong (BL40) on the back side which appeared at a high frequency in the treatment of KOA [54].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that alternative treatments, such as acupuncture, moxibustion, and acupotomy, benefit patients with KOA. [19–24]…”
Section: Inrtoductionmentioning
confidence: 99%
“…compared with no treatment. 34 An RCT published in 2021 found that electroacupuncture was more effective than manual acupuncture in improving pain, stiffness, and disfunction at the end of 8-week treatment. 35 These two RCTs might change the clinical practice of acupuncture for KOA.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published large sample randomized controlled trial (RCT) found that 4‐week manual acupuncture improved the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) total score and pain, stiffness, and function subgroup scores in weeks 4 and 16 compared with no treatment 34 . An RCT published in 2021 found that electroacupuncture was more effective than manual acupuncture in improving pain, stiffness, and disfunction at the end of 8‐week treatment 35 .…”
Section: Introductionmentioning
confidence: 99%